ANALISIS PERSEPSI PASIEN TENTANG PENYAKIT KANKER - Savitri, Wenny; Hutasoit, Masta (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Prevalence of cancer in Indonesia is increasing and needs special attention from health care providers. Perception of cancer is a mental representation regarding patients’ beliefs about cancar. The positive or negative representation influences patients’ decision to manage their illness which leads to quality of life. Objective: This study aimed to investigate cancer patients’ perceptions of their illness and to analyse causal attribution of demographic and clinical characteristic of the patients and their satisfaction with cancer information to the perceptions. Methods: Sixty adult cancer survivors at Panembahan Senopati Bantul Hospital of Yogyakarta Indonesia were recruited in cross-sectional study completing a demographic and health-related data form, the Satisfaction with Cancer Information Profile Questionnaire and Brief Illness Perceptions Questionnaire. The data were analyzed using descriptive statistics and path analysis. Results: Most patients had negative perceptions to cancer. The perceptions of cancer had direct causal association and influenced by patients satisfaction of cancer information provided by health care providers (β= .609, p = .043). Conclusion: Petients perceived cancer as a threat to their lives and was significantly influenced by patients’ satisfaction of cancer information, therefore health care providers need to adjust information to the cancer patients to meet their needs.